Young Phoenix from Family Ashes : An Exploration of Post Traumatic Growth in Broken Home Adolescents - Anndiny Anastasya Handayani; Harjune Dinho Benyqno; Praditha Revalia Julaikah Saputri; Rifdah Shafa Nafilah; Nanda Audia Vrisaba (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Parental divorce can have a significant impact on children, affecting many aspects of their lives including behavior and emotional well-being, triggering trauma. However, trauma does not always have a negative impact, but some make individuals grow stronger. Therefore, this study aims to explore post traumatic growth in adolescents from broken home families due to parental divorce. This research uses a qualitative approach with a case study, through in-depth interview techniques and observation using research instruments designed based on Tedeschi's post traumatic growth theory. The results of this study indicate that the different family backgrounds of the subject's caregivers after parental divorce and the values held by the subject are determining factors in the development of aspects of post traumatic growth in the subject, so that positive development in adolescents who face difficulties, emphasizing the importance of a supportive environment in facilitating recovery and growth after trauma.